2023
DOI: 10.3390/ijms241210338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manual Lymphatic Drainage on the Concentrations of Selected Adipokines, Cytokines, C-Reactive Protein and Parameters of Carbohydrate and Lipid Metabolism in Patients with Abnormal Body Mass Index: Focus on Markers of Obesity and Insulin Resistance

Abstract: The aim of the study was to assess the impact of manual lymphatic drainage (MLD) on the parameters of carbohydrate metabolism, lipid metabolism and the level of selected adipokines and cytokines in people with abnormal body mass index (BMI). In addition, an attempt was made to assess the optimal cut-off values of serum concentrations of the biochemical parameters studied in identifying the risk of obesity and insulin resistance (IR). The study included 60 subjects who underwent 10 and 30 min long MLD sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…This is a therapeutic massage technique specifically developed to activate the lymphatic system and facilitate the removal of surplus fluid from tissues. Studies have shown that MLD can temporarily reduce swelling and improve the appearance of cellulite, though results are often short-lived and require regular sessions for maintenance [ 52 ]. The technique involves gentle, rhythmic massaging to encourage lymph flow.…”
Section: Reviewmentioning
confidence: 99%
“…This is a therapeutic massage technique specifically developed to activate the lymphatic system and facilitate the removal of surplus fluid from tissues. Studies have shown that MLD can temporarily reduce swelling and improve the appearance of cellulite, though results are often short-lived and require regular sessions for maintenance [ 52 ]. The technique involves gentle, rhythmic massaging to encourage lymph flow.…”
Section: Reviewmentioning
confidence: 99%
“…Another adipokine is Adiponectin, secreted by fat cells [10,20]. It performs metabolic functions in the liver, by activating glucose transport and increasing insulin sensitivity, and skeletal muscles, by enhancing insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Adiponectin in adipose tissue increases glucose uptake and affects fat metabolism. It exhibits a protective effect in some inflammatory diseases by affecting inflammatory cells [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation